Deteksi Dini Lesi Prakanker dan Kanker Rongga Mulut Pasien Perokok Elektrik di Departemen Ilmu Penyakit Mulut RSGMP Universitas Jember - Erlinda Rahma Kurniawati (Fakultas Kedokteran Gigi, 2025)
E-cigarettes are becoming popular around the world, especially among teenagers and young adults. However, e-cigarettes are known have negative effects on soft tissues as the first place that comes into direct contact with the aerosols. Oral soft tissue lesions can form due to e-cigarette use, including precancerous and cancerous lesions. For these reasons, early detection can improve the survival of patients at risk of developing oral cancer. Purpose: This study aims to identify the results of early detection of the oral cavity of e-cigarette patients for precancerous lesions and oral cancer in the Oral Medicine Department of the University of Jember Dental and Oral Hospital. Methods: The study was conducted at the Oral Medicine Department of the University of Jember Dental and Oral Hospital, from September to November 2024, with 30 respondents. The study used a descriptive observational method using a cross-sectional design. Early detection is carried out through clinical and advanced examination using VELscope. The results are presented in tabular form and described in the written form. Results: No oral mucosal abnormalities were found that could potentially become malignancies, either precancerous or oral cancer lesions. Cases of abnormalities found, such as smoker’s melanosis (40,54%), nicotine stomatitis (13,51%), keratosis (10,81%), and no lesions were found (35,14%). Conclusion: Research conducted on electric smoker patients at the Oral Medicine Department of the University of Jember Dental and Oral Hospital in September - November 2024 with 30 respondents, that is no oral mucosal abnormalities were detected that had the potential for malignancy, both precancerous or oral cancer
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 5 Juni 2026_Kurnadi
Keywords: e-cigarettes; early detection; precancerous lesions; oral cancer lesions